Strength-training periodization: No effect on swimming performance in well-trained adolescent swimmers - Schumann, M.; Notbohm, H.; Bäcker, S.; Klocke, J.; Fuhrmann, S.; Clephas, C. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To assess the effects of periodized versus nonperiodized dry-land strength training (DLST) on indices of swimming performance in well-trained adolescent swimmers. Methods: Sixteen athletes (10 boys and 6 girls; age 14.9 [1.1] y) performed similar endurance training for 16 weeks (29.1 [7.5] km·wk-1). During weeks 1 to 7, all athletes additionally performed 2 or 3 times weekly whole-body DLST (3 × 6-10 repetitions at 75-85% 1-repetition maximum [1RM]). Thereafter, the DLST frequency was maintained, but athletes were stratified into periodized (experimental, n = 9) and nonperiodized (control, n = 7) DLST groups. The experimental group performed maximal (3 × 3-4 repetitions at 85-90% 1RM) and explosive DLST (throws and unloaded jumps), while in the control group, DLST was maintained. Results: Swimming time at 4 mmol·L-1 of blood lactate improved after 7 weeks in both the experimental (+2.6% [1.8%], P = .033) and the control groups (+3.2% [2.4%], P = .081) and plateaued thereafter. Ten-meter start improved in both the experimental (-3.6% [2.5%], P = .039) and the control groups (-5.1% [2.2%], P = .054) throughout the entire intervention. Both groups improved in maximal weight lifted in half-squat (experimental, +19.6% [14.9%], P = .021; control, +25.7% [18.4%], P = .054) and bench press (experimental, +14.1% [4.8%], P = .018; control, +19.3% [11.1%], P = .051). Countermovement-jump height increased only in the experimental group throughout the intervention (+19.4% [7.0%], P = .024). The associations for the pooled changes in half-squat performance and 4 mmol·L-1 of blood lactate were statistically significant (r = .560, P = .024). Conclusions: The findings do not support the superior effects of DLST periodization in adolescent swimmers. However, the association between improvements in lower-body strength and swimming performance still indicates the importance of muscle strength in this age group.